Pengaturan Pendirian Perusahaan Penanaman Modal Asing (PMA) di Indonesia - Gusti Ngurah Sudarma Yuda; I Nyoman Putu Budiartha; Ni Made Puspa Sutari Ujianti (Fakultas Hukum, Universitas Warmadewa, 2021)
Investment has a very important function in terms of improving the development of the state's economy. This investment is an activity carried out by the business world in order to improve the standard of living of the community. The research aims to explain the arrangement of agreements for the establishment of foreign investment companies in the era of regional autonomy and to describe the settlement of disputes in foreign investment. The research method was normative legal research with a problem approach using a statutory approach and a conceptual approach. The data sources used were primary and secondary legal materials. The results of this study indicatde the existence of PMA during the regional autonomy era, the policies taken by the Bali Provincial BKPMD / BPM to attract investors to invest in the Bali area, especially the Bali Province BKPMD / BPM are still guided by the Letter of the Deputy for National Entrepreneurship Development, BPM Number S-35. / DU-5BKPM / 2001 concerning the field of promotion and international cooperation in investment and dispute resolution for foreign investment who commit violations according to Law Number 25 of 2007 is pursued by means outside the general court (non-litigation) through arbitration and through the judiciary ( litigation).